EFEKITIVITAS REBUSAN DAUN SIRIH MERAH UNTUK PENYEMBUHAN LUKA PERINEUM DI WILAYAH KERJA PUSKESMAS PANIPAHAN KECAMATAN PASIR LIMAU KAPAS KABUPATEN ROKAN HILIR - Yana, Epi; Ruspita, Rika; Ekdeni Aifa, Wira; Mardiya, Rizka (Ensiklopedia Research and Community Service Review, 2025)
Caring for perineal wounds in mothers after giving birth is useful for reducing discomfort, maintaining cleanliness, preventing infection and speeding up the healing of perineal suture wounds. The aim of the research was to determine the effectiveness of boiled red betel leaves for healing perineal wounds in the Panipahan Community Health Center Working Area, Pasir Limau Kapas District, Rokan Hilir Regency. The type of research is quantitative and quasi-experimental design with one group pretest-posttest. The population is postpartum mothers and the sample is 12 people, with purposive sampling. The research instruments were observation sheets and boiled red betel leaves. Data analysis uses univariate and bivariate.  The univariate results show that the average maternal wound healing score on the first postpartum day as assessed by REEDA before red betel leaf decoction therapy was 7.14 and after red betel leaf decoction therapy the score decreased to 0.35. The results of the paired sample t test obtained a p-value of 0.000 < 0.05. The conclusion is that red betel leaf decoction is effective for healing perineal wounds in the Panipahan Health Center Working Area. It is hoped that the Panipahan Community Health Center can improve services, especially in the field of postpartum maternal care, to accelerate wound healing by providing education and counseling about the importance of using boiled red betel leaves.Keywords: Red Betel Leaves, Perineal Wounds